2021
DOI: 10.3390/en14154408
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Two-Phase Flow Heat Transfer Performance and Instability with Discrete Heat Sources in Parallel Channels

Abstract: With the rapid development of integrated circuit technology, the heat flux of electronic chips has been sharply improved. Therefore, heat dissipation becomes the key technology for the safety and reliability of the electronic equipment. In addition, the electronic chips are distributed discretely and used periodically in most applications. Based these problems, the characteristics of the heat transfer performance of flow boiling in parallel channels with discrete heat source distribution are investigated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Using the VOF model along with the level set (LS) scheme, the authors in [6] defined a criterion for estimating bubble departure diameter during FB of refrigerant R314a. Hu et al [7] similarly investigated HTC and flow instabilities during FB of R314a using VOF. They concluded that a discrete heat source was better at suppressing the instability than a continuous heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Using the VOF model along with the level set (LS) scheme, the authors in [6] defined a criterion for estimating bubble departure diameter during FB of refrigerant R314a. Hu et al [7] similarly investigated HTC and flow instabilities during FB of R314a using VOF. They concluded that a discrete heat source was better at suppressing the instability than a continuous heat source.…”
Section: Introductionmentioning
confidence: 99%
“…), and even the lengths of intermolecular interactions in fluids. Such device features have promising applications in various scientific fields, including microelectronic device cooling [2][3][4], water filtration and salinification [5], biomedicine and biosensing [6], fluid-based electronics, and energy storage and conversion [7].…”
Section: Introductionmentioning
confidence: 99%